Package of practices for organic mustard in Bundelkhand - Gangwar, B; Jain, Deepmala (Indian Farming, 2023)
India is the largest rapeseed-mustard growing country in the world, occupying second position in area and fourth position in production. Rapeseed-Mustard is a rabi annual, drought hardy crop, capable to grow under diverse agro-climatic conditions and different types of soils. Oil content in rapeseed-mustard varies from 33–46% amongst different species and varieties. Mustard oil is agreat affordable alternative of palm oil. Organic farming of mustard is gaining importance in the country in recent years due to increasing soil, human and environmental concerns. The use of chemical fertilizers and pesticides is very low which can be substituted through organic sources. Therefore, growing of crops under organic management using recommended production technologyprovides a very good yield of 25–30 q/ha obtained in Bundelkhand region.